Analisis Kadar Sukrosa dan Gula Pereduksi pada Madu Trigona (Stingless Bee Honey) Menggunakan Metode Luff Schoorl - Raudhatul Hanifa; Rahadian Zainul (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study aims to analyze the levels of reducing sugars and sucrose in Trigona honey using the Luff Schoorl method as a key parameter for assessing honey quality and authenticity. Trigona honey, produced by stingless bees, possesses unique physicochemical characteristics that differ from Apis mellifera honey, thus requiring further scientific investigation of its sugar profile. The analysis was performed at the BSPJI Pekanbaru Laboratory using a titrimetric procedure based on the Luff Schoorl reagent, involving the determination of reducing sugars and sucrose following hydrolysis. The results revealed that the reducing sugar content of the Trigona honey sample was 31.75%, while the sucrose content was 9.6%. These values do not comply with the Indonesian National Standard (SNI 8664:2018), which requires a minimum of 55% reducing sugars and a maximum of 5% sucrose in honey. The non-conformity is presumed to be influenced by factors such as nectar source, high moisture content, premature harvesting, and storage conditions. Nevertheless, the deviation from the standard does not necessarily indicate adulteration but may reflect the natural characteristics of stingless bee honey. This research provides scientific evidence that may contribute to the evaluation of specific quality standards for Trigona honey in Indonesia and serve as a reference for future studies related to authentication and standardization of stingless bee honey products.